2001
DOI: 10.1097/00001756-200108080-00009
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine hydroxylase, but not dopamine beta-hydroxylase, is increased in rat frontal cortex after traumatic brain injury

Abstract: Chronic frontal lobe functional deficits after traumatic brain injury (TBI) may be associated with altered catecholamine systems in the frontal cortex. To test this, tyrosine hydroxylase (TH) and dopamine beta-hydroxylase (DBH) levels were examined by immunohistochemistry and Western blot at 1, 7, 14, and 28 days after TBI or sham surgery. No alterations in DBH levels were observed by Western blot at any time point examined, but there was a significant increase in TH expression 28 days after TBI (optical densi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 19 publications
2
49
1
Order By: Relevance
“…Specifically, the TH signal was seen as a single band of approximately 59 kDa ( Fig. 3A and 4A) and is consistent with previous studies (Soriano et al, 1997;Yan et al, 2001). Consistent with the immunohistochemistry findings using this TH antibody (Fig.…”
Section: Western Blotsupporting
confidence: 92%
See 3 more Smart Citations
“…Specifically, the TH signal was seen as a single band of approximately 59 kDa ( Fig. 3A and 4A) and is consistent with previous studies (Soriano et al, 1997;Yan et al, 2001). Consistent with the immunohistochemistry findings using this TH antibody (Fig.…”
Section: Western Blotsupporting
confidence: 92%
“…These time points were selected on basis of previous studies of DA systems after TBI (Yan et al, 2001(Yan et al, , 2002. Tissue preparation and immunohistochemistry procedures were as previously reported (Yan et al, 2001).…”
Section: Immunohistochemistrymentioning
confidence: 99%
See 2 more Smart Citations
“…Previous work suggests ongoing regional alterations in tissue catecholaminergic concentrations after experimental TBI [19]. Studies from our laboratory have demonstrated chronic alterations in frontal cortex dopamine (DA) system proteins after experimental TBI, including increased tyrosine hydroxylase [43], a protein critical in the synthesis of DA, and decreased DA transporter (DAT), a protein critical for reuptake of DA into presynaptic terminals [44]. Additional work suggests that striatal DAT levels are decreased in males after TBI [38].…”
Section: Introductionmentioning
confidence: 97%